Despair as a Governing Strategy: Australia and the Offshore Processing of Asylum-Seekers on Nauru - Fleay, Caroline; Hoffman, S. (Oxford University Press, 2014)
As part of its efforts to deter the arrival of asylum-seekers by boat to Australia in2001, Prime Minister John Howard’s Coalition Government established the offshore processing of refugee claims. Known as the Pacific Solution, this policy included an agreement with Nauru and Papua New Guinea’s Manus Island for asylum-seekers arriving to Australia by boat to be transported to either of these islands where they would wait in camps while their refugee claims were processed. The majority of the asylum-seekers subjected to offshore processing at this time were held on Nauru, and most had fled Afghanistan. Governmentality, as introduced by Michel Foucault and developed by later scholars, provides insight into the institutions, methods, techniques, strategies, and tactics used by governments to achieve its ends. This article explores Australian Government policy and the experience of Afghan asylum-seekers held on Nauru from 2001 using a governmentality approach. Given that people seeking asylum in Australia are once again being transported to Nauru and Papua New Guinea, this time initiated by a Labor Government and continued by the current Coalition Government, this article’s findings are pertinent for insight into understanding current Australian policy.